Diagnosa Cedera dan Eksternal Cause - Ahmad Ainur Ridho; Muhammad Bintang Saputra; Liss Dyah Dwi Arini (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to assess the distribution, causes, risk factors and prevention strategies of injuries caused by external factors through a literature review. Injuries are a significant health problem and can occur in different age groups and in different geographical locations. The review showed that children and the elderly are the most vulnerable groups to injury, with significant variation in incidence by geographic region. The main causes of injury identified include traffic accidents, falls, physical violence and occupational accidents. Each cause has specific risk factors, such as risky behaviour, unsafe environmental conditions and lack of safety regulations. Effective prevention strategies include education, policy and regulation, engineering and technology, and health interventions. The findings emphasise the importance of a holistic and integrated approach to injury prevention. Recommendations for future research include long-term evaluations, multidisciplinary approaches and improved data access. By understanding the distribution, causes and risk factors of injuries, and implementing effective prevention strategies, we can reduce injury rates and improve the overall quality of life in society.